Non-invasive and quantitative assessment of sudomotor function for peripheral diabetic neuropathy evaluation - Gin, H.; Baudoin, R.; Raffaitin, C.H.; Rigalleau, V.; Gonzalez, C. (Diabetes & metabolism, 2011)
Perturbation of pain sensation is considered one of the major initiating risk factors for diabetic foot ulcer. Sweat dysfunction leading to abnormal skin conditions, including dryness and fissures, can increase foot ulcer risk. The aim of this study was to evaluate Sudoscan™, a new, quick, non-invasive and quantitative method of measuring sudomotor dysfunction as a co-indicator of the severity of diabetic polyneuropathy (DPN). A total of 142 diabetic patients (age 62 ± 18 years, diabetes duration 13 ± 14 years, HbA 1c 8.9 ± 2.5%) were measured for vibration perception threshold (VPT), using a biothesiometer, and for sudomotor dysfunction, using electrochemical sweat conductance (ESC) based on the electrochemical reaction between sweat chloride and electrodes in contact with the hands and feet. Retinopathy status was also assessed, as well as reproducibility between two ESC measurements and the effect of glycaemia levels. ESC measurements in the feet of patients showed a descending trend from 66 ± 17 μS to 43 ± 39 μS, corresponding to an ascending trend in VPT threshold from < 15 V to > 25 V ( P = 0.001). Correlation between VPT and ESC was −0.45 ( P < 0.0001). Foot ESC was lower in patients with fissures, while VPT was comparable. Both VPT and foot ESC correlated with retinopathy status. Bland–Altman plots indicated good reproducibility between two measurements, and between low and high glycaemia levels. Sudoscan™ is a reproducible technique with results that are not influenced by blood glucose levels. Sweating status may be a quantitative indicator of the severity of polyneuropathy that may be useful for the early prevention of foot skin lesions. La perte de sensibilité est considérée comme le facteur de risque majeur « du pied diabétique ». La perturbation de la fonction sudorale favorisant la survenue d’anomalies cutanées (sécheresse de la peau et fissures) peut également augmenter le risque. Le but de cette étude était d’évaluer une nouvelle méthode rapide, non-invasive, et quantitative (Sudoscan™) destinée à mesurer la fonction sudorale comme co-indicateur de la sévérité d’une neuropathie périphérique diabétique. Cent quarante-deux patients diabétiques (âge 62 ± 18 ans, ancienneté du diabète 13 ± 14 ans, HbA 1c 8,9 ± 2,5 %) ont bénéficié d’une mesure du seuil de perception vibratoire avec un biothésiomètre et de la fonction sudorale par mesure au niveau des pieds de la conductance électrochimique résultant de la réaction entre les chlorures de la sueur et des électrodes en contact avec les pieds et les mains. L’atteinte rétinienne a été également déterminée. La reproductibilité entre deux mesures et l’effet du niveau glycémique sur les mesures ont également été évalués. La conductance des pieds passe de 66 ± 17 μS à 43 ± 39 μS quand le seuil de perception vibratoire passe de < 15 V à > 25 V ( P = 0,001) avec une corrélation de −0,45 ( P < 0,0001) entre ces deux paramètres. Chez les patients ayant des fissures, la conductance des pieds est abaissée alors que le seuil de perception vibratoire n’est pas encore discriminant. Ces deux paramètres sont corrélés aux lésions observées au fond d’œil. Un graphe de Bland-Altman indique une bonne reproductibilité pour les conductances électrochimiques des pieds entre deux mesures et entre des mesures à un niveau haut ou normal de la glycémie. Le Sudoscan™ est une méthode reproductible et les résultats ne sont pas influencés par la glycémie. L’évaluation de la fonction sudorale peut constituer un indicateur quantitatif de la sévérité d’une polyneuropathie utile dans la prévention du pied diabétique.